Stigma and attitudes on epilepsy a study: with secondary school students Atitudes e estigma na epilepsia: um estudo com jovens do ensino médio - Brenda A. Reno; Paula T. Fernandes; Gail S. Bell; Josemir W. Sander; Li M. Li (Arquivos de Neuro-Psiquiatria)
PURPOSE: To evaluate whether an inappropriate attitude towards a person having an epileptic seizure contributes to the stigma found in society and whether an appropriate attitude helps to diminish it in the short term; to perform a long term investigation about information remembered and stigma perception after an educational lecture. METHOD: This study was performed in two steps: Step 1. Students of first year of high school of two schools in Campinas completed a questionnaire including the Stigma Scale of Epilepsy following a seizure demonstration. They were divided into three groups: a) one group had a demonstration of proper attitudes towards someone having an epileptic seizure; b) one group was shown incorrect procedures; c) control group. After the completion of the questionnaire, an educational lecture about epilepsy was given. Step 2: six months later, the questionnaire was re-administered. RESULTS: The comparison between the four groups (step 1 and step 2) show a significant difference (Anova (3,339)=2.77; p=0.042). Pairwise comparison using Fisher's Least-Significant-Difference Test showed a significant difference between the group shown incorrect procedures (step 1) versus step 2, and the control group (step 1) versus step 2, but no difference between the group shown correct procedures (step 1) versus step 2. DISCUSSION: Exhibiting proper attitudes towards a person experiencing an epileptic seizure may cause significant differences among the subjects’ degrees of stigma towards people with epilepsy. It is therefore fundamental that there should be de-stigmatization campaigns provided, to correct information and provide appropriate education. OBJETIVO: Investigar se atitudes errôneas tomadas durante uma crise epiléptica contribuem para o estigma na sociedade e, se a conduta de seguir atitudes corretas ajuda a diminuí-lo a curto prazo e se a participação em palestra informativa também contribui para a diminuição do estigma a longo prazo. MÉTODO: O trabalho foi realizado em duas etapas: 1. Foi aplicada a Escala de Estigma na Epilepsia (EEE), acrescida de algumas perguntas gerais sobre epilepsia, em alunos do primeiro ano do Ensino Médio de duas escolas (pública e particular) em Campinas. Os sujeitos foram divididos em 3 grupos, sendo: a) grupo que presenciou atitudes corretas durante a crise epiléptica; b) grupo que presenciou atitudes errôneas durante a mesma; c) grupo controle que só respondeu ao questionário, e depois, todos foram reunidos para palestra educativa. 2. Depois de seis meses, o mesmo questionário foi aplicado nos sujeitos que participaram da palestra educativa da primeira etapa. RESULTADOS: A comparação entre os quatro grupos (passo 1 e 2) mostrou diferença significativa [(ANOVA (3,339)=2,77; p=0,042). Análise estatística (Fisher) mostrou diferenças significativas entre o grupo que presenciou atitudes incorretas (etapa 1) e a etapa 2, entre o grupo controle (etapa 1) e a etapa 2, e não encontrou diferenças entre o grupo que presenciou atitudes corretas (etapa 1) e a etapa 2. DISCUSSÃO: Os sujeitos expostos a condutas adequadas durante uma crise epiléptica, bem como a informações corretas sobre epilepsia demonstraram menor percepção de estigma. Com isso, concluímos que intervenções educacionais devem ser realizadas para se tentar mudanças a longo prazo.